Comprehensive Care Improvement for Oncologic Fever and Neutropenia from a Pediatric Emergency Department. Issue 2 (12th March 2021) - Kuehnel, Nicholas A.; McCreary, Erin; Henderson, Sheryl L.; Vanderloo, Joshua P.; Hoover-Regan, Margo L.; Sharp, Brian; Ross, Joshua
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Rapid time to antibiotics (TTA) for pediatric patients with fever and neutropenia in an emergency department decreases in-hospital mortality. Additionally, national guidelines recommend outpatient antibiotic management strategies for low-risk fever and neutropenia (LRFN). This study had two specific aims: (1) improve the percent of patients with suspected fever and neutropenia who receive antibiotics within 60 minutes of arrival from 55% to 90%, and (2) develop and operationalize a process for outpatient management of LRFN patients by October 2018. Methods: Using Lean methodologies, we implemented Plan-Do-Check-Act cycles focused on guideline development, electronic medical record reminders, order-set development, and a LRFN pathway as root causes for improvements. We used statistical process control charts to assess results. Results: The project conducted from July 2016 to October 2018 showed special cause improvement in December 2016 on a G-chart. Monthly Xbar-chart showed improvement in average TTA from 68.5 minutes to 42.5 minutes. A P-chart showed improvement in patients receiving antibiotics within 60 minutes, from 55% to 86.4%. A LRFN guideline and workflow was developed and implemented in October 2017. Conclusions: Implementation of guidelines, electronic medical record reminders, and order sets are useful tools to improve TTA for suspected fever and neutropenia. Utilizing more sensitive statistical process control charts early in projects with fewer patients can help recognize and guide process improvement. The development of workflows for outpatient management of LRFN may be possible, though it requires further study.